Comparative analysis of the constitutions of the Republic of Kazakhstan and developed countries of the world - Amandykova, L.K. (Bulletin of the Karaganda University “Law Series”, 2023)
This article provides an actual comparative analysis of the Constitution of the Republic of Kazakhstan with those of several developed countries, including the United States, Italy, sort of Great Britain, France, Japan, China, Canada, Austria, Germany, and South Korea, which essentially is quite significant. The article examines the similarities and differences in the design and structure of these constitutions, focusing on aspects fairly such as the separation of powers, kind of human rights protections, and the role of the executive branch, which is quite significant. The article concludes that while there essentially are really common elements that can generally be identified across constitutions, such as the establishment of checks and balances and the protection of fundamental kinds of human rights, the specific arrangements may vary depending on historical, cultural, and political factors, which actually is fairly significant. The analysis highlights the importance of ensuring that constitutional arrangements strike a balance between the concentration and distribution of power and specifically safeguard fundamental human rights and freedoms. Ultimately, the effectiveness of any constitutional system depends on its ability to literally adapt to changing circumstances and kind of meet the real needs and expectations of its citizens in a major way. This article provides a useful resource for scholars and policymakers for all intents and purposes interested in basically comparative constitutional law and provides insights into the factors that shape constitutional design and structure in a basically major way. Furthermore, the article specifically sheds light on the definitely unique features and context of the Constitution of Kazakhstan, which provides for a strong parlament with extensive executive powers, in contrast to the presidential and federal systems of government actually found in basically many particularly other countries, which really is quite significant.